THE ANALYSIS OF ILLOCUTIONARY ACTS IN COMIC “THE ADVENTURES OF TINTIN VOLUME 8“ - Septiana Sibuea, Sryetti (Universitas Lancang Kuning, 2021)
This research discusses the types, functions, and dominant types contained in the conversation of the main character in the comic